Abstract Filipe+Braumann COMPSTAT 2008 - Filipe, Patrícia A. (2009)
Oral communication at the international conference COMPSTAT 2008 (18th International Conference in Computational Statistics, Porto, August 2008). Web page: http://www.fep.up.pt/compstat08/ Study and parameter estimation for one and several trajectories (including bootstrap methods) of stochastic differential equation models for the growth of individual animals in randomly fluctuating environments.